Regulation of the cellulose synthase-like gene family by light in the maize mesocotyl - van Erp, Harrie; Walton, Jonathan D (Planta, 2009)
The cellulose synthase-like (ZmCSL) gene family of maize was annotated and its expression studied in the maize mesocotyl. A total of 28 full-length CSL genes and another 13 partial sequences were annotated; four are predicted to be pseudogenes. Maize has all of the CSL subfamilies that are present in rice, but the CSLC subfamily is expanded from 6 in rice to 12 in maize, and the CSLH subfamily might be reduced from 3 to 1. Unlike rice, maize has a gene in the CSLG subfamily, based on its sequence similarity to two genes annotated as CSLG in poplar. Light regulation of glycan synthase enzyme activities and CSL gene expression were analyzed in the mesocotyl. A Golgi-localized glucan synthase activity is reduced by ~50% 12 h after exposure to light. β-1,4-Mannan synthase activity is reduced even more strongly (>85%), whereas β-1,4-xylan synthase, callose synthase, and latent IDPase activity respond only slightly, if at all, to light. At least 17 of the CSL genes (42%) are expressed in the mesocotyl, of which four are up-regulated at least twofold, seven are down-regulated at least twofold, and six are not affected by light. The results contribute to our understanding of the structure of the CSL gene family in an important food and biofuel plant, show that a large percentage of the CSL genes are expressed in the specialized tissues of the mesocotyl, and demonstrate that members of the CSL gene family are differentially subject to photobiological regulation.